A MICRO BUSINESS DEVELOPMENT MODEL THAT UTILIZES GREEN INNOVATION ANTECEDENT VARIABLES TO ENHANCE SUSTAINABLE PERFORMANCE IN MSMES LOCATED IN BINTAN REGENCY - Charly Marlinda; Satriadi Satriadi; Nanda Kristia Santoso (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The aims of this research is to know, understand, and test the influence and interrelationship of the antecedent factors of green innovation on sustainable performance. This type of research is verifiable descriptive research. This research was conducted on 364 marine-based MSMEs in Bintan Regency. Data collection was carried out using a questionnaire with a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). The conceptual model is presented in Figure 1 and verified using the PLS (Partial Least Square) method with SmartPLS 3.0 software. The results of the study show that first, there is a positive and significant relationship between technological capabilities and green innovation. Organizations with strong technological capabilities are better able to adopt environmentally friendly practices, which support more efficient product and process development. Second, CSR has a positive influence on green innovation. Companies that are active in CSR practices tend to be more open to innovations that support sustainability. However, not all CSR initiatives contribute significantly, especially if they are not grounded in a sincere commitment to sustainability. Third, green innovations have been proven to have a positive and significant effect on sustainable performance. Organizations that implement green innovation not only meet environmental demands but also improve operational efficiency and reputation. However, the success of green innovation must be integrated with the overall business strategy to achieve maximum impact. Fourth, the effect of moderation of environmental dynamics is not significant on sustainable performance. This indicates that external changes may not be strong enough to affect the relationship between green innovation and sustainable performance, and many organizations have not fully adapted to those dynamics